Nature conservation in Poland and the geographer’s role as an employee in a national park - Partyka, Józef (Turystyka w badaniach podstawowych, 2023)
The aim of the article is to briefly present the issues of nature protection in Poland, and then to present against this background the role of a geographer as an employee of a national park, making a significant contribution to nature conservation. The author shares his many years of experience working in the Ojców National Park (48 years), describes the more important tasks and key competences he performs. Among them, he mentions keeping nature documentation for the needs of the park protection plan, scientific research carried out in the field of his specialty, collecting bibliography and photographic documentation, and educational and publishing activities. It indicates which of them may also be useful in other sites of area protection and what additional forms of further education are necessary.